2019
DOI: 10.1111/inm.12629
|View full text |Cite
|
Sign up to set email alerts
|

Exploring therapeutic engagement with individuals with a diagnosis of personality disorder in acute psychiatric inpatient settings: A nursing team perspective

Abstract: Individuals with a diagnosis of personality disorder (PD) face negative attitudes and are often deemed harder to care for than individuals with other diagnoses. To improve care and engagement with services, it is essential to understand the ways general psychiatric nursing staff approach this client group. This research aims to examine the ways inpatient psychiatric nursing staff therapeutically engage with individuals with a diagnosis of PD. Focus groups were conducted with Registered Mental Health Nurses (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Studies have reported that this skewed perception also extends to healthcare professionals who have a tendency to display negative attitudes towards this patient group and perceive them as manipulative (Westwood & Baker, 2010). Therefore, to improve inpatient care for this patient population, structured admissions with a clear goal including case management and discharge plans have been described as therapeutic (Acford & Davies, 2019). Acford and Davies (2019) also described that structured admissions are helpful for the staff and provided a framework on how to support patients in a constructive way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that this skewed perception also extends to healthcare professionals who have a tendency to display negative attitudes towards this patient group and perceive them as manipulative (Westwood & Baker, 2010). Therefore, to improve inpatient care for this patient population, structured admissions with a clear goal including case management and discharge plans have been described as therapeutic (Acford & Davies, 2019). Acford and Davies (2019) also described that structured admissions are helpful for the staff and provided a framework on how to support patients in a constructive way.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to improve inpatient care for this patient population, structured admissions with a clear goal including case management and discharge plans have been described as therapeutic (Acford & Davies, 2019). Acford and Davies (2019) also described that structured admissions are helpful for the staff and provided a framework on how to support patients in a constructive way.…”
Section: Introductionmentioning
confidence: 99%
“…Short‐term positive change following educational intervention (Acford & Davies, 2019 [M]; Davies et al, 2014 [L]; Ebrahim et al, 2016 [M]; Lamph et al, 2018 [M]), ES+++ for “emotional reaction.” Evidence for sustained change hampered by low retention…”
Section: Resultsmentioning
confidence: 99%
“…There was ample evidence from studies that measured attitudes were amenable to change over the short term in relation to personality disorder (Acford & Davies, 2019 ; Davies et al, 2014 ; Dickens et al, 2018 ; Ebrahim et al, 2016 ; Lamph et al, 2018 ), self‐harm antipathy (Patterson et al, 2007a , 2007b ) and mental disorder/substance misuse co‐morbidity (Munro & Baker, 2007 ; Munro et al, 2007 ). Effect sizes for pre‐test to post‐test change were typically large except that for the Self‐Harm Antipathy Scale which was moderate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation